Periodontal, demographic and systemic condition characteristics of patients treated at a dental school - Fabio Anibal Goiris; Rodrigo Rocha; Julio Moreira; Fabio Andre dos Santos (Revista Sul-Brasileira de Odontologia, 2013)
The aim of this study was to evaluate the relations among: age, reasons for dental appointment, systemic conditions, use of medicines and periodontal disease, in patients assisted in the Periodontal Clinic at the Dental School of the Center of Higher Education of Campo Gerais (short Cescage – Ponta Grossa, Brazil), during 2007-2009. Material and methods: A total of 183 dental files were obtained and 100 were included in the study. The following tests were applied: student t, Mann-Whitney (quantitative variables) and Qui-square (χ2) (qualitative variables). The level of significance adopted was of 5%. Results: The main reason for dental appointment was not the need of periodontal treatment, but tooth pain and dental aesthetics. In relation to the systemic condition, women presented more systemic alterations in comparison with men, showing higher prevalence of diabetes and hypertension. In relation to the drugs, only 20% of men used systemic drugs, while 52% of women used them. Dental plaque showed similar percentage between genders, but bleeding on probing was lower in women. Concerning to periodontal disease the prevalence of pocket probing depth (until 4 mm) was equivalent in both genders, and the buccal area of the mouth showed a higher prevalence than the labial area. Considering periodontal pocket probing depth (7 mm or more), the result was similar in both genders and the buccal area of the mouth showed higher prevalence that the labial area. Conclusion: Anamnesis and clinical examination accomplished in the periodontal clinic can establish some demographic, clinical and systemic disease patterns related to the presence of the periodontal disease in patients seeking treatment at dental school clinics.